A Four-tier Test to Identify Students’ Conceptions in Inheritance Concepts - Noviah Rosa Firdaus; Tjandra Kirana; Endang Susantini (IJORER : International Journal of Recent Educational Research, 2021)
Identification of students' conceptions is an important step before developing suitable learning methods to improve students' understanding. One of the best way to identify students’ conception is the use of diagnostic test. Therefore, the development of diagnostic tests were important in the teaching and learning process to help the teacher determine the students’ conceptions, wheater they have scientific conceptions, lack of knowledge, or misconception. The aim of this research is to develop a valid and reliable four-tier diagnostic test to identify students’ conceptions in inheritance. The research method consists of three main stages: define content, obtaine information about students’ conception, and develop the four-tier test. The result from the research demonstrated that the four-tier test that was developed, was valid and reliable instrument in diagnosing students’ conception in inheritance concepts.